Dinamika Implementasi Kebijakan Transformasi Eks PNPM Menjadi BUM Desa Bersama di Kecamatan Sungai Tarab - Ulya Fitri; Dewi Dahlan; Rasyidah Mustika; Rindi Ramadhani (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
This study describes the dynamics of the policy of transferring former PNPM to Village Owned Enterprises (BUM Desa). This transfer is based on Government Regulation No. 11 of 2021 concerning the BUM Desa. This research was conducted in the former PNPM Sungai Tarab District. The purpose of this study is to examine how this transformation took shape and what were the obstacles faced by UPK DAPM Lenggogeni, who was a former PNPM, in transforming into a Joint Village-Owned Enterprise (BUM Desa bersama). The research method used is descriptive qualitative research method. Interviews were conducted with the Head of DAPM Lenggogeni, Sungai Tarab District, Secretary of Nagari, Head of Sungai Tarab Sub-District and Head of Community Empowerment Division of Tanah Datar DPMD. The results obtained are that looking at aspects of policy implementation by Edward III in the form of non-smooth communication between the former PNPM managers and the PMD PPKB service due to firm refusal from the manager became a dynamic in itself. Then for the aspect of human resources there is a shortage of personnel from the agency, as well as financial resources that must be taken from the ex-PNPM managing fund assets, making it difficult for the PMD PPKB agency to continue the transformation phase. The disposition of the agency is quite clear even though some SOP instructions have not been provided, as well as aspects of fragmentation that have not been developed between village institutions. This made it difficult to form an established organizational structure as a result of the implementation of the transformation of the former PNPM into BUM Desa bersama. None of the four stages of transformation have been carried out, so it is feared that in the remaining two months or so this policy cannot be implemented in Sungai Tarab District.